An Incidental Case Of Combined Infection Of Tuberculosis And Paratuberculosis In Cross Breed Cow - Singh, N.D.; Banga, H.S.; Gadhave, P.D.; Goyal, A.; Brar, R.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Tuberculosis (TB) and paratuberculosis (JD) are highly infectious diseases mostly caused by M. bovis and Mycobacterium avium sub sp. respectively (Radostitis et al. 2000). Both the diseases are prevalent worldwide and cause substantial economic losses in livestock production especially in developing countries (Pollock and Neill, 2002). There are number of reports of both these diseases separately (Jones et al., 1997). Case reports of combined infection are relatively rare. The present study describes occurrence of combined case of both bovine tuberculosis and paratuberculolsis in a cross breed cow.